Qualitative Study On Drug Users Class IIa Bulukumba Drugs - Misrawati; Asri; Tenriwati (Comprehensive Health Care, 2019)
Illegal drugs are solid or liquid substances, gases that cause physical and psychological changes in the body, almost all drugs affect the central nervous system, drugs act on the brain and can affect anesthesia, view the emergence of side effects and the high persistence to use illegal drugs without being prescribed by a doctor and can cause drug addiction or addiction. Some factors cause drug users, namely environmental factors, family factors and social factors, and 179 drug users in Bulukumba class IIA prisons.The purpose of this study: is to know the factors of the use of illegal drugs in class IIA Bulukumba. The research design used was a qualitative study with a phenomenological approach through in-depth interview techniques. Data was collected in the form of records and results of interviews. Respondents in this study amounted to 6 people using illegal drugs who were selected by purposive sampling. In this study, several theme analysis results were obtained, namely (1) first try (2) the influence of family factors (3) the influence of social factors. Conclusion: Drug users occur as a result of the first try factor, high curiosity, and friend invitations, drug users occur due to family factors, and drug users occur as a result of free sex.